Capacity Choice of Dams under Rivalry Use and Externalities - Harold Houba; Kim Hang Pham Do; Xueqin Zhu (Tinbergen Institute, 2014)
This paper studies the relation between optimal dam capacity and water management under rivalry uses and externalities. We extend the hydropower generation model, based on Haddad (2011), by including the competing use of water resource, non-linear building cost of dam capacity and externalities in a welfare optimization model. We obtain the optimal dam capacity for multi-functional dams such as providing infrastructure for industrial and households water use, conjunctive use of hydropower generation and irrigation; storing water in the wet season for use in the dry season, and mitigating flooding damages. The optimal solution shows that optimal dam capacity is characterized by the marginal benefits of hydropower generation, the marginal costs of flooding damages, and the constraining factors. Moreover, the optimal water management can be achieved by using derived sea sonal prices in a decentralized manner.
Keywords: C71; C72; D62; 330; OR in environment and climate change; river-basin management; dam capacity; welfare optimization; externalities